Salmonella y Shigella a partir de muestras fecales en la población Santa Rosa, Maracaibo-Venezuela. - Sandrea-Toledo Lisette; Avila-Roo Yeiny; Paz-Montes América; Corpas-Guerrero Carmen; Petit-Capriles Kalina; Ocando-Vilchez Newlsa (Kasmera, 2007)
Abstract: The gastrointestinal infections, there represent worldwide some of the major reasons of morbid-mortality, principally in the underdeveloped countries, being common in those populations with scanty conditions associate sanitary as the population indigenous to Saint Rose. The purpose of this research was to detect the presence of Salmonella and Shigella from fecal samples in the town of Santa Rosa. It processed 245 stool samples of individuals between ages 2 months to 83 years with or without diarrhea, which was conducted technique coprocultive (8) and testing for susceptibility to antimicrobial agents following the methodology described by the CLSI (5). Of the total number of samples processed, 7 of them (2.9%) were positive for the genera Salmonella and Shigella. Salmonella was detected in 85.7%, identifying serogroups Salmonella enterica Group B in 66.7% and Salmonella enterica group C1 to 33.3%, while Shigella was isolated in a 14.3%, being S. flexneri the only species found. On the evidence of resistance to antimicrobial-resistant Salmonella proved Ampicillin, Tetracycline and Amoxicillin/Acid Clavulánico with 16.7% for each. Shigella showed a pattern of resistance to Ampicillin, Tetraciclina, Chloramphenicol, Amoxicillin/Acid Clavulánico and Trimethoprim Sulfametoxazol. Despite the precarious conditions in the sector of Santa Rosa, the incidence of bacterial pathogens is low, compared to other areas with similar characteristics of life.